Protecting Digital Footprints: A Selective Web History Sanitization Tool for Domestic Violence Survivors - Ahmed, Rozha Kamal; Lips, Silvia; Rashid, Zryan Najat (Kurdistan Journal of Applied Research, 2025)
This study introduces a novel solution that is designed to protect the privacy of domestic violence survivors when seeking online support. It enables survivors to access essential online resources without leaving digital footprints that may lead to further abuse by their violent partners. The study employs the principles of the design science framework to develop and evaluate a system for selective web history sanitization. The implemented system effectively deletes traces related to support websites while preserving unrelated browsing history to avoid the abuser’s suspicion, ensuring both usability and privacy. This work contributes a novel artifact that addresses a critical societal challenge, providing domestic violence survivors with a secure, adaptive, and privacy-preserving tool to seek online supports with confidence. It offers a significant step forward in protecting and empowering vulnerable populations, particularly those with limited technical expertise in the digital age. Additionally, this work offers practical insights for organizations that support survivors by advocating for the development and use of privacy-focused tools and practices to make their digital services more effective and safer.